Understanding the Zion Christian Church (ZCC) Pilgrims - Kruger, Martinette; Saayman, Melville (International Journal of Tourism Research, 2016)
The purpose of this research is to analyse the motives and segment the Zion Christian Church (ZCC) pilgrims to the Zion City of Moria in South Africa during Easter according to these motives. Seven motives were identified: spiritual fulfilment, inner peace, inner healing, faith exploration, congregational togetherness, personal fulfilment and religious participation. Based on these motives, pilgrims were grouped into three distinctive clusters namely devotees, explorers and seekers. These clusters differ significantly based on their motives, socio-demographic and behavioural characteristics, thereby showing that these pilgrims are not a homogeneous market. This research contributes to the knowledge base regarding characteristics and behaviour of these specific and distinctive pilgrims in South Africa. Copyright (C) 2014 John Wiley & Sons, Ltd.
paid
Keywords: South Africa; Zion Christian Church; attractions; cluster analysis; factor analysis; issues; motives; pilgrims; religious tourism; tourism; visitors